2006
DOI: 10.1103/physrevlett.96.097008
|View full text |Cite
|
Sign up to set email alerts
|

Nearly Free Electrons in the Layered Oxide SuperconductorAg5Pb2O6

Abstract: We present first measurements of quantum oscillations in the layered oxide superconductor Ag5Pb2O6. From a detailed angular and temperature dependent study of the de Haas-van Alphen effect we determine the electronic structure and demonstrate that the electron masses are very light, m* approximately 1.2me. The Fermi surface we observe is essentially that expected of nearly free electrons--establishing Ag5Pb2O6 as the first known example of a monovalent, nearly free electron superconductor at ambient pressure.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Our dHvA experiment, reported in full in reference [6], revealed that the FS of Ag 5 Pb 2 O 6 is nearly free electron-like, as shown in Fig. 1.…”
Section: Experimental Fermi Surfacesupporting
confidence: 55%
“…Our dHvA experiment, reported in full in reference [6], revealed that the FS of Ag 5 Pb 2 O 6 is nearly free electron-like, as shown in Fig. 1.…”
Section: Experimental Fermi Surfacesupporting
confidence: 55%
“…Indeed, in many metals, resistivity is found to saturate to a value close to ρ MIR at sufficiently high temperatures, in clear contrast to the prediction of ρ ∝ T based on the high-temperature Boltzmann theory. For Ag 5 Pb 2 O 6 , the MIR limit is estimated as ρ MIR ∼ 730 µΩcm, based on the values k F = 0.53 Å −1 determined from the quantum oscillation experiment 20,21 and d ∼ a = 5.93 Å. 18 Therefore, ρ c of Ag 5 Pb 2 O 6 is still smaller than the MIR limit in the present temperature range, manifesting the validity of semiclassical treatments of transport phenomena.…”
Section: A Resistivitymentioning
confidence: 69%
“…For B c, the orbital of the cyclotron motion is perpendicular to the c axis. Because the Fermi surface of Ag 5 Pb 2 O 6 is nearly axial-symmetric around the c * axis 19,20 (Fig. 1(c)), the cyclotron orbits are circles around the c * axis in k-space and v z (k(t)) is time-independent along each orbit.…”
Section: Magnetoresistancementioning
confidence: 99%
See 1 more Smart Citation
“…Despite its low T c of 52.4 mK, 3 the material has attracted significant attention because of its nearly-free-electron nature in the normal metallic phase. 4,5 Typical nearly-free-electron materials, such as alkali and noble metals, do not exhibit superconductivity at ambient pressure, except Li, which has an extremely low T c of 0.4 mK. 6 Therefore, Ag 5 Pb 2 O 6 has been considered an ideal model system for investigating superconductivity without the effects of the complicated electronic structure.…”
Section: Introductionmentioning
confidence: 99%